Evaluación de la metodología de ensayo acelerado de barras de mortero ASTM C 1260 para detectar agregados potencialmente reactivos y las medidas de mitigación de la reacción álcali-sílice ASTM C 1567 (2018)
The alkali-silica reaction is defined as a phenomenon produced by the alkalis (sodium or potassium) of the cement, which react with the silica present in certain aggregates, forming a gel that under conditions of humidity generates internal microcracks and stresses. In the present article the results of a research project are exposed in which the potential reactivity of three aggregates of the Colombian territory in combination with two types of cements and two water-cement ratios was evaluated, with the ASTM C 1260 bar test. mortar. From the reactive samples, the effectiveness of cementitious materials to mitigate the alkali-silica reaction was evaluated in the ASTM C 1567 mortar bar test. Finally, the mechanical behavior of samples of mortar, such as the resistance to compression, bending and modulus of elasticity, compared to specimens with reactive aggregates was analyzed. and not reactive, concluding that the alkali-silica reaction increases as the aggregate-cement ratio increases and this depends on the mineralogical composition of each aggregate. On the other hand, the mitigating materials used, such as flying ash F, microsilica and metakaolin, are competent to reduce the alkali-silica reaction in a certain proportion of replacement; The mechanical properties most affected by the alkali-silica reaction are the module elastic and flexural strength, and compressive strength is affected in lower percentage over time.